1997
DOI: 10.1038/40073
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Southern Ocean surface-water stratification to low atmospheric CO2 concentrations during the last glacial period

Abstract: The nitrogen-isotope record preserved in Southern Ocean sediments, along with several geochemical tracers for the settling fluxes of biogenic matter, reveals patterns of past nutrient supply to phytoplankton and surface-water stratification in this oceanic region. Areal averaging of these spatial patterns indicates that reduction of the CO 2 'leak' from ocean to atmosphere by increased surface-water stratification south of the Polar Front made a greater contribution to the lowering of atmospheric CO 2 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
438
2
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 548 publications
(485 citation statements)
references
References 34 publications
43
438
2
2
Order By: Relevance
“…Such a shift from a CO 2 source to a CO 2 sink between pre-industrial time and present is documented for the Weddell Sea located in the Atlantic Sector of the Southern Ocean (Hoppema, 2004). According to the first hypothesis, permanent surface water stratification south of the APF, possibly in response to sea-ice expansion, acted as a major contributor to the CO 2 drop during the last glacial period (Francois et al, 1997;Sigman and Boyle, 2000). The stratification of the upper water column would have reduced vertical mixing and thus prevented the ventilation of CO 2 -rich deep water.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such a shift from a CO 2 source to a CO 2 sink between pre-industrial time and present is documented for the Weddell Sea located in the Atlantic Sector of the Southern Ocean (Hoppema, 2004). According to the first hypothesis, permanent surface water stratification south of the APF, possibly in response to sea-ice expansion, acted as a major contributor to the CO 2 drop during the last glacial period (Francois et al, 1997;Sigman and Boyle, 2000). The stratification of the upper water column would have reduced vertical mixing and thus prevented the ventilation of CO 2 -rich deep water.…”
Section: Introductionmentioning
confidence: 99%
“…Francois et al, 1997;Crosta and Shemesh, 2002;Robinson et al, 2005). Additionally, Francois et al (1997) and Frank et al (2000) measured authigenic uranium and observed a maximum in authigenic uranium content within sediments deposited during the LGM at site PS1768. The authors interpreted the authigenic uranium peak to indicate a decrease in bottom water oxygen concentration and concluded that during the LGM the water column south of the APF must have been less ventilated by increased stratification.…”
Section: Clues For Stratification In the Southern Ocean During The Lamentioning
confidence: 99%
See 3 more Smart Citations